2022
DOI: 10.1186/s13033-022-00558-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural stigma and its impact on healthcare for borderline personality disorder: a scoping review

Abstract: Background People with Borderline Personality Disorder (BPD) and their carers/families continue to experience structural stigma when accessing health services. Structural stigma involves societal-level conditions, cultural norms, and organizational policies that inhibit the opportunities, resources, and wellbeing of people living with attributes that are the object of stigma. BPD is a serious mental illness characterized by pervasive psychosocial dysfunction including, problems regulating emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 123 publications
0
18
0
1
Order By: Relevance
“…MSI-BPD, BEST), in line with clinical guidelines, young people were not automatically diagnosed with BPD if they met criteria (National Collaboration Centre for Mental Health, 2009; Swales, 2022). Instead, a discussion was had with young people and their families about the diagnosis, its strengths and limitations, differential diagnoses such as complex post-traumatic stress disorder, and the potential stigma associated with BPD (Klein et al ., 2022; Lamb et al ., 2018; Swales, 2022). The use of diagnostic terminology was guided by what was identified as clinically helpful in collaboration with the young person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSI-BPD, BEST), in line with clinical guidelines, young people were not automatically diagnosed with BPD if they met criteria (National Collaboration Centre for Mental Health, 2009; Swales, 2022). Instead, a discussion was had with young people and their families about the diagnosis, its strengths and limitations, differential diagnoses such as complex post-traumatic stress disorder, and the potential stigma associated with BPD (Klein et al ., 2022; Lamb et al ., 2018; Swales, 2022). The use of diagnostic terminology was guided by what was identified as clinically helpful in collaboration with the young person.…”
Section: Discussionmentioning
confidence: 99%
“…BPD is not typically diagnosed with diagnostic manuals in those under 18 years old. There is understandable hesitance to associate specific struggles for adolescents with this label, as personality is still developing and to protect against the potential stigma and criticisms related to the BPD construct (Kaess et al ., 2014; Klein et al ., 2022; National Collaboration Centre for Mental Health, 2009; Swales, 2022). However, emerging BPD symptoms in adolescents are associated with an increased likelihood of long-term difficulties with BPD and high costs to young people’s health (Chanen et al ., 2017; Winograd et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been widely reported that the capacity of existing health services to meet the complex needs of patients with BPD is limited (Iliakis et al, 2019; Warrender et al, 2021; Zimmerman, 2015). A review completed in 2022 (Klein et al, 2022) found that myths regarding the untreatability of patients with BPD continue to perpetuate the stigmatizing culture, attitudes and practices within health‐care systems. Despite BPD being treatable with evidence based psychotherapy (Lynch et al, 2007), clinicians frequently encounter barriers such as limited service availability of these treatments (Carrotte et al, 2019; Hermens et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, this study is the first to take a comparative cross‐sectional measure of attitudes towards patients with BPD, within different stages of a formal psychiatry training programme. Given the well‐established link between positive perception and improved treatment outcomes (Klein et al, 2022), it is imperative that clinicians maintain empathy and treatment optimism towards patients with BPD. This study has shown that more advanced psychiatry trainees have less empathy, reduced treatment optimism and a more negative attitude towards patients with BPD, when compared to junior trainees.…”
Section: Discussionmentioning
confidence: 99%
“…This is related to greater treatment reluctance and past abuses, particularly in areas such as intellectual disability where there is universal suspicion of all kinds of experimentation (Oliver et al, 2002). In personality disorder, there are particular problems associated with stigma (Klein et al, 2022; Ring & Lawn, 2019).…”
Section: Ensuring a Representative Populationmentioning
confidence: 99%